The The Influence of Training and Career Development on Employee Performance in RSUD Pandan Arang Boyolali District: Pengaruh Pelatihan dan Pengembangan Karir terhadap Kinerja Pegawai di RSUD Pandan Arang Kabupaten Boyolali - Butuh Damai Saputra,; Bagus Ajie Cahyadi,; Nadrotul Falah Ramadhan ,; Alean Kristiani Hegy Suryana,; Arin Sulistyowati, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the influence of partial and simultaneous training, career development on the performance of employees of Pandan Arang Hospital, Boyolali Regency. The associative approach method aims to understand the relationship between independent and dependent variables. The sample consisted of 88 employees at the Tehnik Hospital for data collection using questionnaires and multiple linear regression analysis. The results showed that the training partially had a significant effect on employee performance with a significance value of 0.000 < 0.05. Career development has a significant effect on employee performance with a significance value of 0.000 < 0.05. Simultaneously, training and career development have a positive and significant effect on employee performance with a significance value of 0.000 < 0.05. Based on the determination coefficient test, it shows a value of 0.710, meaning that employee performance is influenced by training and career development 71% and influenced by other variables 29%.